Pengaruh Instagram Ocean Dream Samudra Ancol terhadap Minat Berkunjung Kembali - Poppy Poppy; Hana Ulinnuha; Fajar Anugrah Subhi (Lembaga Pengembangan Kinerja Dosen, 2024)
Alongside the advancement of the period, it is normal that the utilization of web-based media can give different sorts of data to its clients. As well as giving intriguing and inventive data with the goal that it can draw in light of a legitimate concern for the Indonesian individuals to visit Sea Dream Samudera Ancol. This study expects to decide the impact of Instagram advancement on interest in getting back to Sea Dream Samudra Ancol. Specialists utilized quantitative strategies with basic direct relapse investigation helped by the SPSS 22 for windows program and dispersed surveys to 125 vacationers who got back to Sea Dream Samudera Ancol. The aftereffects of this study show that Instagram online media can impact the variable of return to intrigue, which is 68.9% while the excess 31.1% is affected by different factors which are excluded from this review.